Active thrombin produced by the intestinal epithelium controls mucosal biofilms - Jean-Paul Motta (Nature Portfolio, 2019)
The roles played by thrombin in the human intestinal mucosa are unclear. Here, the authors show that the commensal microbiota modulates epithelial production of active thrombin, which controls biofilm growth and contributes to protection of the mucosa from bacterial invasion.